UU Antimonopoli Indonesia: Suatu Telaah Orientasi dan Implikasinya terhadap Perilaku Pelaku Bisnis dan Konsumen - muryati marzuki (Jurnal Hukum IUS QUIA IUSTUM, 2001)
To minimalize the effect ofthis code from unfairness conduct of bussinessmen, KPPU and court should control its application. However, the making ofthis code has contributed positively the economical aspect of national development.